Optimizing Hospital Management System Through The Kanban Method: A Review of Current Evidences - I Ketut Dian Lanang Triana; Ni Putu Emy Darma Yanti; Vip Paramarta; Putu Dyah Candra Agustina (Journal of Advanced Nursing and Health Systems Innovation, 2025)
Background – Hospitals, as essential providers of healthcare services, face significant challenges in managing diverse inventories, including pharmaceuticals, medical equipment, and daily operational supplies. Inefficient inventory management often leads to increased costs and resource wastage, underscoring the need for systematic approaches to enhance efficiency. Objectives – This study aimed to review the literature on the application of the Kanban method in hospital inventory management and to evaluate its potential benefits in cost reduction and waste minimization. Methods – A literature review was conducted using a replicable protocol to identify relevant peer-reviewed articles indexed in Google Scholar. The search was restricted to publications in English and Indonesian from January 2020 to January 2025. Boolean search strategies were employed with keywords including Kanban Method, hospital inventory management, cost reduction, and efficiency. Eligible articles were thematically analyzed to synthesize the findings. Results – The review highlights that the Kanban method, originally developed for manufacturing industries, can be effectively adapted to hospital settings. Its implementation demonstrates potential to optimize resource utilization, reduce operational costs, and alleviate waste production. However, challenges remain, particularly cultural resistance among healthcare staff and the need for systematic planning and organizational commitment to ensure successful adoption. Conclusion – The Kanban method offers a viable and effective approach for improving hospital inventory management. This findings offer practical insights for hospital administrators and policymakers seeking cost-effective and sustainable inventory management strategies, while also identifying gaps for future empirical research.